Learning innovations from research to practice: dilemmas in the field. (2nd January 2019) - Koh, Elizabeth; Lee, Shu-Shing
ABSTRACT: Educational research has been at the forefront of educational transformation by examining how learning occurs and enabling ways of learning notably through designing and implementing learning innovations. However, learning innovations are complex. There are multiple embedded contexts involving classrooms, schools, communities, homes and the wider education landscape. This article is a reflection from two researcher-innovators who have partnered with schools and teachers in their innovation and change journeys in Singapore. We have encountered several tensions amongst teachers and raise three of those dilemmas relating to stakeholder perspectives, sustainability and the customisation of the innovation. Learning innovations in the field, while creating various dilemmas for the key teacher stakeholder, translates research to practice and enables teachers to learn and grow their professionalism. An effortful resolution is required.